Review of blenniid fishes from Fernando de Noronha Archipelago, Brazil, with description of a new species of Scartella (Teleostei: Blenniidae) - Rangel, Carlos A.; Mendes, Liana F. (Zootaxa, 2009)
Species of the family Blenniidae from Fernando de Noronha Archipelago (03°51’S, 32°26’W), an oceanic island 345 km off northeastern Brazil, are reviewed in this study, which includes the description of a new species of Scartella. The new species differs from its congeners by the combination of the following characters: well-marked diagonal dark line just under the eye, tiny black spots on the head, small black and white spots along the body, 14 segmented dorsal-fin rays, 15 segmented anal-fin rays, and 23 caudal vertebrae. This is the second Scartella species described from Brazilian oceanic islands.